2013
DOI: 10.12965/jer.130059
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes reduces the cognitive function with the decrease of the visual perception and visual motor integration in male older adults

Abstract: This study investigated the influence of diabetes on cognitive decline between the diabetes and non- diabetes patients and identified the associations between diabetes and cognitive function, visual perception (VP), and visual motor integration (VMI). Sixty elderly men (67.10± 1.65 yr) with and without diabetes (n= 30 in each group) who were surveyed by interview and questionnaire in South Korea were enrolled in this study. The score of Mini-Mental State Examination of Korean version (MMSE-KC), Motor-free Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
1
Order By: Relevance
“…With regard to suitable types of exercise, the ACSM recommends aerobic exercise, such as walking, hiking, or strength training, and mental and physical exercise, such as tai chi or balancing exercises. Additionally, Yun et al (2013) reported that it is more effective to engage in low-intensity exercise for a long period than it is to engage in high-intensity exercise. Conversely, Kim and Kim (2003) reported that high-intensity exercise is effective; therefore, there may be differences in exercise effects for older women depending on the intensity of the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to suitable types of exercise, the ACSM recommends aerobic exercise, such as walking, hiking, or strength training, and mental and physical exercise, such as tai chi or balancing exercises. Additionally, Yun et al (2013) reported that it is more effective to engage in low-intensity exercise for a long period than it is to engage in high-intensity exercise. Conversely, Kim and Kim (2003) reported that high-intensity exercise is effective; therefore, there may be differences in exercise effects for older women depending on the intensity of the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of previous studies, VMI has been suggested as an effective instrument for measuring intellectual ability, language ability, various brain abnormalities ( Belmont and Belmont, 1980 ). In addition to that, it has been suggested for cognitive function of the old people ( Hall et al, 1996 ) and the old people diabetic patients ( Yun et al, 2013 ). However, few studies have been applied VMI to detect cognitive function of the old people so far ( Yun et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, it has been suggested for cognitive function of the old people ( Hall et al, 1996 ) and the old people diabetic patients ( Yun et al, 2013 ). However, few studies have been applied VMI to detect cognitive function of the old people so far ( Yun et al, 2013 ). This is because there is currently no proven VMI evaluation tool available in the field although it is effective in predicting changes in cognitive function of the old people.…”
Section: Introductionmentioning
confidence: 99%
“…Visual-motor integration (VMI) is a vision-related cognitive function that is a degree of coordination between visual perception and finger-hand movements ( Bolk et al, 2018 ). The Beery VMI is a valuable measure from children ( Bolk et al, 2018 ) to older adults and can be an early indicator of cognitive decline ( Yun et al, 2013 ). However, it strongly focused on childhood academic achievement ( Osorio-Valencia et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%